Anxiety And Risk Of Cardiovascular Disease - Rama Agastya, Komang; Agung Riatmojo, Andi; Abdi Akbar, Rauchsan (Rifa'Institute, 2021)
Anxiety is a normal emotion that is owned by every individual. Pathologically increased anxiety can not only give rise to other anxiety disorders but can also lead to other mental illnesses. Anxiety is a type of mental disorder that is quite common in Europe, Switzerland, Iceland, Norway in 2010 it was found that the prevalence for 12 months was 14% and 61.5 million people were affected. According to WHO in the global population with anxiety disorders in 2015 the percentage was 3.6% and it was more common in women with a percentage of 4.6% compared to 2.6% for men. Individuals with symptoms of anxiety are likely to experience the effects of interference that can lead to metabolic syndrome. Metabolic syndrome leads to progressive and clustering of several metabolic risk factors that directly increase the risk of death from cardiovascular disease (CVD, type 2 diabetes mellitus). last year from 10% to 63.2%. Anxiety disorders appear to be caused by the interaction of bio-psychosocial factors. Genetic susceptibility interacts with stressful situations or the presence of trauma to produce a clinically significant syndrome. Treatment measures include pharmacological, psychological, and combination therapies. all are therapeutic measures for all anxiety disorders, selective serotonin is a first line agent for several anxiety disorders, including panic disorder, social anxiety, generalized anxiety disorder.Psychotherapy and pharmacotherapy should be given and both therapies are equally effective. The choice in determining the therapy given must be considered according to the severity of the disorder.